A impressão 3D como ferramenta no ensino de embriologia e anatomia do sistema respiratório: um estudo quase experimental - Barreto, Jackeline Osterno de Carvalho (2024)
3D printing is an effective tool for teaching anatomy, as it has a positive impact on learning outcomes and satisfaction levels. The pedagogical success of 3D printing appears to be better when it reproduces complex anatomical areas that are difficult to visualize on cadavers. Based on these premises, the objective of this study was to investigate the success of using 3D printed models of the respiratory system on medical academic learning. An exploratory, quasiexperimental study was conducted with 421 students. Nine 3D models related to embryology and anatomy of the respiratory system (lower airways) were modeled and printed on a resin printer. For the present study, two groups were created: the first that participated in a traditional class (control) and the second that participated in a traditional class with the resources of 3D models (3D group). To measure learning, a structured test with 20 questions was used, before and after the traditional class (control), with the use of 3D models (3D group). The Mann Whitney test was used to analyze the data, and those with p < 0.05 were considered significant. In the qualitative analysis, interviews were conducted and recorded for Content Analysis. It was observed that the majority of students were female, with an average age of 21.23 ± 0.32 years. A statistically significant difference in the correct answers of the 3D group was also observed when compared to the traditional group (p < 0.05). The average correct answers in the pre-test were 3.46 ± 0.10 when compared to the post-test, with an average of correct answers of 6.30 ± 0.13. The readings of the transcribed interviews allowed us to identify that the teachers' perceptions were positive, affirming the success of the pedagogical practices using the 3D models in the students' learning process. The teachers also stated that the material was of excellent quality and that there were no errors, and that they even provided corrections for some anatomical structures contained in the textbooks. 3D printing is a potentially disruptive technology that can improve surgical education and clinical practice, making the teaching of anatomy more engaging when it is associated with the identification of structures that cannot be visualized in the embryo and cadaver. The use of 3D models has proven to be a relevant tool for enhancing traditional teaching, which, combined with practical classes, improves the teaching and learning of anatomy